Theory of Mind in Bipolar Disorder, with Comparison to the Impairments Observed in Schizophrenia - Mitchell, Rachel L. C.; Young, Allan H. (Frontiers in Psychiatry, 2016)
Our ability to make sense of information on the potential intentions and dispositions of others is of paramount importance for understanding their communicative intent, and for judging what an appropriate reaction might be. Thus anything that impinges on this ability has the potential to cause significant social impairment, and compromise an individual’s level of functioning. Both bipolar disorder and schizophrenia are known to feature theory of mind impairment. We conducted a theoretical review to determine the extent and types of theory of mind impairment in bipolar disorder, and evaluate their relationship to medication and symptoms. We also considered possible mediatory mechanisms, and set out to discover what else could be learnt about the impairment in bipolar disorder by comparison to the profile of impairment in schizophrenia. The literature established that in bipolar disorder (i) some form of theory of mind impairment has been observed in all mood states, including euthymia, (ii) the form of theory of mind assessed and task used to make the assessment influence the impairment observed, and (iii) there might be some relationship to cognitive impairment, although a relationship to standard clinical variables was harder to establish. What also became clear in the literature on bipolar disorder itself was the possible relationship of theory of mind impairment to history of psychotic symptoms. Direct comparative studies including patients with schizophrenia were thus examined, and provided several important directions for future research on the bases of impairment in bipolar disorder. Particularly prominent was the issue of whether theory of mind impairment could be considered a candidate endophenotype for the psychoses, although current evidence suggests this may be premature. The differences in impairment across schizophrenia and bipolar disorder may, however, have genuine differential effects on social functioning and the likely success of remediation.